Is Mandatory Carbon Disclosure Associated With Real Carbon Performance: A Study of South African Companies Listed on JSE - NYAHUNA, Thomas; DOORASAMY, Mishelle; NOMLALA, Bomi (PT Keberlanjutan Strategis Indonesia, 2023)
With the increasing importance of carbon disclosure as a tool to reduce carbon emissions, the enduring question remains whether carbon disclosure reduces carbon emissions. This paper analyzes the rapport between